2023
DOI: 10.3390/ijms24076429
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis of Heat Stress Response in Brassica rapa L. ssp. pekinensis with Improved Thermotolerance through Exogenous Glycine Betaine

Abstract: Chinese cabbage (Brassica rapa L. ssp. pekinensis) is sensitive to high temperature, which will cause the B. rapa to remain in a semi-dormancy state. Foliar spray of GB prior to heat stress was proven to enhance B. rapa thermotolerance. In order to understand the molecular mechanisms of GB-primed resistance or adaptation towards heat stress, we investigated the transcriptomes of GB-primed and non-primed heat-sensitive B. rapa ‘Beijing No. 3’ variety by RNA-Seq analysis. A total of 582 differentially expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
0
1
0
Order By: Relevance
“…In the process of responding to heat stress, 1720 and 6178 DEGs were identified in Clematis lanuginosa and Clematis crassifolia, respectively [45]. In the Brassica genus, the number of DEGs in response to heat stress is correlated with various factors, including cultivar, temperature, treatment duration, and tissue type [46][47][48][49]. In our study, 11,579 and 14,707 DEGs were identified in response to heat stress treatment for 4 and 12 h, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…In the process of responding to heat stress, 1720 and 6178 DEGs were identified in Clematis lanuginosa and Clematis crassifolia, respectively [45]. In the Brassica genus, the number of DEGs in response to heat stress is correlated with various factors, including cultivar, temperature, treatment duration, and tissue type [46][47][48][49]. In our study, 11,579 and 14,707 DEGs were identified in response to heat stress treatment for 4 and 12 h, respectively.…”
Section: Discussionsupporting
confidence: 46%
“…Compared with the metabolomic data, JA and SA were significantly downregulated in the plant hormone transduction pathway, while IAA and ERF signaling were upregulated in the plant hormone transduction pathway, which was consistent with the transcriptome results. Recently, Quan et al reported that the thermotolerance of Brassica rapa in heat stress responses could be improved through exogenous glycine betaine (GB) [ 30 ]. In this study, ABA, SA, auxin, and cytokinin (CK) hormones were either up– or downregulated in GB–primed Brassica rapa plants under heat stress.…”
Section: Discussionmentioning
confidence: 99%